2016
DOI: 10.5604/17322693.1199987
|View full text |Cite
|
Sign up to set email alerts
|

The cellular receptors of exogenous RNA

Abstract: One of the key determinants of survival for organisms is proper recognition of exogenous and endogenous nucleic acids. Therefore, high eukaryotes developed a number of receptors that allow for discrimination between friend or foe DNA and RNA. Appearance of exogenous RNA in cytoplasm provides a signal of danger and triggers cellular responses that facilitate eradication of a pathogen. Recognition of exogenous RNA is additionally complicated by fact that large amount of endogenous RNA is present in cytoplasm Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recently, a growing body of literature has shown that some exogenous RNAs can be recognized by a myriad of receptors in host eukaryotic cells and that such small non-coding RNAs can be transmitted between different species to induce signal interference in a transboundary manner (Reniewicz et al 2016 ). Just like microbes and hosts, symbiotic or pathogenic relationships between various organisms may be mediated by this pattern of cross-species communication (Liang et al 2013 ).…”
Section: The Role Of Exogenous Mirnasmentioning
confidence: 99%
“…Recently, a growing body of literature has shown that some exogenous RNAs can be recognized by a myriad of receptors in host eukaryotic cells and that such small non-coding RNAs can be transmitted between different species to induce signal interference in a transboundary manner (Reniewicz et al 2016 ). Just like microbes and hosts, symbiotic or pathogenic relationships between various organisms may be mediated by this pattern of cross-species communication (Liang et al 2013 ).…”
Section: The Role Of Exogenous Mirnasmentioning
confidence: 99%
“…6). This also applied to diverse LPS datasets and responses to TLR ligands, CpG oligonucleotide (a ligand for TLR9, which mediates cellular response to unmethylated CpG dinucleotides in bacterial DNA or R848 (a ligand for TLR7/TLR8 both of which recognize RNA released from pathogens that enter the cell by endocytosis [150]) ( Fig. 6).…”
Section: Upregulated Genes In the Ad Hippocampus Are Enriched In Genementioning
confidence: 99%
“…Others are designed to sense viral DNA or RNA. These include intracellular TLRs (TLR3, 8,9), EIF2AK2 (eukaryotic translation initiation factor 2 alpha kinase 2), often known as pkr, RIG-I (coded by retinoic acid-inducible gene 1 = DDX58), MDA5 (Melanoma Differentiation-Associated protein; coded by IFIH1) and LGP2 (coded by DEXH-box helicase 58 = DHX58) [150,153,154]. Indoleamine 2,3-dioxygenase 1 (IDO1) diverts tryptophan metabolism to N-formyl-kynurenine; (away from serotonin production).…”
Section: Upregulated Genes In the Ad Hippocampus Are Enriched In Genementioning
confidence: 99%